Lack of requirement for cell cooperation in the antibody response to DNP conjugated to levan. - Desaymard, C; Feldmann, M (1975)
The cellular basis of the antibody response to dinitrophenylated levan (DNP-LE) was investigated using a combination of in vivo and in vitro techniques. The results indicated that the induction of the primary response to DNP-LE is independent of the function of macrophages or T cells. However, these cells may regulate the response to DNP-LE (as for other T-independent antigens), as suggested by the prolongation of the response by adjuvants. No evidence of collaboration between carrier (LE)-reactive and hapten (DNP)-reactive B cells in the induction of the response to DNP-LE was obtained (either by inducing tolerance to LE (in vivo or in vitro) or culturing in the presence of excess LE). Thus DNP-LE, like other thymus-independent antigens (e.g., DNP-polymerized flagellin, DNP-Ficoll) may trigger B cells directly. © 1975.